Two-Dimensional Physical Modelling of the Northern Breakwater of Leixões Harbour. Case Study - F. Veloso Gomes (2009)
Leixoes Harbor, near Porto, Portugal, has undergone various improvements over recent decades, especially an expansion inland with excavation for new docks, the raising, and seaward extension of the original breakwater, and the construction of a new submerged breakwater to protect the head of the breakwater extension. Faced with demanding goals and the need for new strategies, the Leixoes Harbor authority decided that the operational conditions of oil terminal "A" needed to be improved. In order to meet those requirements eleven alternative configurations were built and tested in a two-dimensional physical model to compare performance for the same regular wave conditions in regard to stability and the overtopping phenomena. Each configuration was also tested for different tide levels. This paper presents the characteristics and results of those tests.